The burden of heat in arid regions of the Middle East: an analysis from Jordan and Kuwait - Yazan Alwadi; Barrak Alahmad (IOP Publishing, 2024)
The Middle East, with its vast arid landscape, is facing escalating health risks due to intensifying heat under climate change. Kuwait and Jordan, two representative countries from the region, have no heat action plan in place. This study aims to (1) quantify the mortality burden of extreme heat in these countries, and hence (2) identify critical temperature thresholds. We collected 17 years of daily mortality records from 2000 to 2016 in Amman, Jordan, and the entire state of Kuwait. We fitted a time series design restricted to the summer months (June-August) for each location. We used distributed lag non-linear models to estimate non-linear associations and lagged effects of temperature on mortality. We then calculated attributable mortality for a range of temperature percentiles. We analyzed a total of 56 654 (39 996 all-cause deaths in Amman and 16 658 non-accidental deaths in Kuwait). Kuwait's average summer temperature (38.7 °C) was higher than Amman (26.5 °C). In Kuwait, 202.1 (95% eCI: 17.7, 344.8) attributable heat deaths occurred over 79 d at temperatures above 41.9 °C (>95th percentile), averaging 2.6 heat deaths per day. Amman experienced 500.7 (95% eCI: 17.7, 344.8) attributable heat deaths over 77 d at temperatures above 30.75 °C, with an average of 6.5 deaths per day. This study equips Kuwait and Jordan with critical data to develop and implement targeted heat action plans. The two Middle Eastern countries face extreme heat challenges and are undergoing serious demographic changes with an influx of migrant workers and refugees. We provide an essential quantification of the mortality burden attributable to extreme heat in Kuwait and Jordan, two countries in the Middle East facing unprecedented heat and yet without existing heat action plans. Policymakers face the question of which thresholds represent negligible risk and which cannot be ignored. By analyzing 56 654 deaths, we reveal the number of deaths per day attributable to specific temperatures. This study presents the first step towards establishing targeted heat action plans to mitigate the health risks posed by intensifying heat. The methods used for Kuwait and Amman can be replicated in similar Middle Eastern countries.